(untitled) (Analele Universitatii din Bucuresti – Seria Istorie, 2024)
Starting with the late 1980ʹs and early 1990ʹs, the field of Western historiography was pervaded by studies on the history of memory against the background of mentalities, the birth of the history of present time and the struggle of oral history to promote itself (time of roots, genealogies, commemorations); it was also the time for a growing interest in an alternative history of Africa built upon memories. Museums felt empowered to interrogate current histories, while the older ones revisited the very concepts upon which they had been previously built. Memories felt compelled to question history – and to rectify it. Certain researchers felt obliged to bring forth the memorial constructions. While in Europe memories were invited to permanently defy history, in Africa their task was, from the beginning, that of investing history with truth. Very scarce were here the invitations to relativism. Memories in Africa brought with them a familiar past that was allegedly colonized and suppressed Furthermore, waking up dormant memories from before the recent, Western colonial past was part of the identity building process in Africa: such narratives justified the individual via his/her ancestors, ethnic group peers and generations. On top of that, local intellectuals built on the national and continental identity. Based on the common roots, the emerging African discourse blamed recent history for the rupture with the long durée. Celebration and commemoration are still the barometers of existing, different types of memories (individual, communities, official). The controversial heritage of juxtaposed memories requires a separate interpretation. The Kermel Square in downtown Dakar, Senegal, is such an example. The walls of the main building and the surrounding building of colonial French architecture are overlapped with imprints of the more recent national memory, and the latter is the sworn enemy of the former. Each nation-state has its own heroes and places of memory, while few remember when the stories associated with them were born. We are now left with just their compulsory, ceremonial re-visitations.